Public service media, innovation policy and the 'crowding out' problem. Issue 3 (3rd July 2021) - Herzog, Christian; Meese, James
ABSTRACT: Public service media organisations manage the challenges they face as they transition to a converged environment by innovating in the areas of distribution, programming, and engagement. Many commercial media companies critique public service innovation and argue that it is 'crowding out' the private market. Focusing on public service media organisations in Germany and Australia, this article examines the relationship between innovation, regulation and resilience. We argue that while the Australian model of innovation performs a vital role for the domestic media industry, it does not always contribute to the long-term resilience of individual innovations brought out by the Australian Broadcasting Corporation. Conversely, while innovation is hamstrung by layers of bureaucracy in Germany, once innovations developed by Second German Television are legally approved, they operate in a relatively uncontested manner. To explain the findings, we propose a comparative framework consisting of four factors: size, public/private divide, regulatory frameworks and legal traditions.